PENILAIAN KINERJA DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KABUPATEN BONE - Hamid, Abdul; Arman, Agus; Suhendra, Suhendra; Nurmiati, Nurmiati; Lubis, Bastian (Universitas Patria Artha, 2022)
This study aims to determine and analyze the financial performance of the Public Works and Spatial Planning Office of Bone Regency in 2018 - 2020. This study uses a value for money model which is a financial performance analysis tool for public sector organizations with ratios consisting of: economic ratios, efficiency ratio, and effectiveness ratio. The results showed that the Public Works and Spatial Planning Office in 2018-2020 based on the concept of value for money in general had shown good performance where the average economic ratio in 2018-2020 at the Bone District Public Works and Spatial Planning Service was 86, 61%, which means it is economical, then the average efficiency ratio is 90.90% which means it is efficient and the average effectiveness ratio shows a figure of 126.23% which means it is effective.